Board Characteristics And Firm Performance In Malaysia - Tabatabaeighods, Seyed Mehdi (2011)
This study intends to investigate the relationships between several board characteristics namely board size, CEO duality, board meeting, independent, chairman independence. financial expertise and gender diversity and firm performance.